A new concept for temporal gating of synchrotron X‐ray pulses. (5th February 2021) - Schmidt, D.; Bauer, R.; Chung, S.; Novikov, D.; Sander, M.; Pudell, J.-E.; Herzog, M.; Pfuetzenreuter, D.; Schwarzkopf, J.; Chernikov, R.; Gaal, P.
Abstract : A new concept for temporal gating of synchrotron X‐ray pulses based on laser‐induced thermal transient gratings is presented. Abstract : A new concept for temporal gating of synchrotron X‐ray pulses based on laser‐induced thermal transient gratings is presented. First experimental tests of the concept yield a diffraction efficiency of 0.18%; however, the calculations indicate a theoretical efficiency and contrast of >30% and 10 −5, respectively. The full efficiency of the pulse picker has not been reached yet due to a long‐range thermal deformation of the sample after absorption of the excitation laser. This method can be implemented in a broad spectral range (100 eV to 20 keV) and is only minimally invasive to an existing setup.